Raw meat business activities in Kuala Lumpur, 1884-1929 - Shapiza Sharif; Arba’iyah Mohd Noor; Masitah Mohammad Yusof (Penerbit UKM, 2025)
This article will examine a different dimension by highlighting raw meat business activities in Kuala Lumpur between 1884 and 1929. Much research has focused on mining activity since the early exploration of Kuala Lumpur by Raja Abdullah, thereby overshadowing other economic activities at that time. Although it may seem unusual for a British-administered town to have a raw meat business activity, the reality is that such activities were indeed organized in Kuala Lumpur. This study focuses on buffaloes and pigs, as both animals held significant economic value at that time. Furthermore, article focuses on the factors that led to the emergence of the raw meat business activities in Kuala Lumpur. This article will also discuss how slaughterhouses, cold storage and fresh markets, which served as distribution medium for meat, helped drive the growth of this business. Therefore, this article will show how the raw meat business activities operated between 1884 and 1929 in Kuala Lumpur. This study used a historical method based on primary and secondary sources from various archives and libraries.